Multiple Cellulase System from Streptomyces antibioticus - Enger, M. D. (1965)
Enger, M. D. (North Dakota State University, Fargo), and B. P. Sleeper. Multiple cellulase system from Streptomyces antibioticus. J. Bacteriol. 89:23–27. 1965.—Starch-block zone electrophoresis was used to isolate five electrophoretically distinct, active cellulolytic components (I to V) from the crude extracellular cellulase system of Streptomyces antibioticus (strain C2A). Agar diffusion precipitin analyses demonstrated the immunological identity of components I, II, and III, and the nonidentity of IV and V with each other and with I to III. Kinetic studies of the purified enzymes showed a sharp decrease in the viscosity of the substrate, carboxymethylcellulose, with only a small increase in reducing sugars. These results indicated that all five enzymes are endocellulases.